Islamic Management and Leadership at the KH Ahmad Dahlan Sipirok Islamic Boarding School - Arianto, Wahyu; Syafnan; Siregar, Balyan Oslerking (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2024)
This research to explore the management and Islamic leadership at the KH Ahmad Dahlan Sipirok Islamic Boarding School. Using a qualitative approach, this research identifies various challenges faced in implementing effective management and leadership based on Islamic values. Data were collected through in-depth interviews and participatory observations with leaders, administrators, and students. The results indicate several issues, such as limited human resources, lack of transparency in financial management, and dynamics of internal conflicts. These findings are expected to provide insights into the development of management and leadership in Islamic educational institutions.